Antimicrobial Analysis and Characterization of P(3HB) Films Containing Essential oils - Rech, Chaiane Regina; Martelli, Silvia Maria; Silva, Bárbara Ellen Bagnara e; Brabes, Kelly Cristina da Silva (Orbital: The Electronic Journal of Chemistry, 2018)
Several studies have focused on the development of new materials for food packaging with the incorporation of antimicrobials such as essential oils. Thus, the present work aimed to develop biodegradable and antimicrobial films based on PHB incorporated with essential oils, named: melaleuca, cinnamon and citronella and also to characterize these films through the Fourier Transform Infrared Technique (FTIR). The films, containing 10, 20 and 30% (w/w) of essential oils, were microbiologically tested by agar-diffusion method against six species. The films containing melaleuca and citronella did not inhibit the microbial growth of any microorganisms tested. Unlike the films containing 20 and 30% of cinnamon that inhibited the growth of almost all microorganisms except Salmonella sp. The FTIR spectra of melaleuca and citronella overlap with those of PHB and it was not possible to observe the characteristic bands. The cinnamon spectrum shown characteristic bands of cinnamaldehyde, the main component of this oil. Through the FTIR technique the incorporation of the cinnamon oil into the polymer matrix can be verified. Microbiological analyzes showed that PHB film with 20 and 30% of cinnamon presented better antimicrobial activity. DOI: http://dx.doi.org/10.17807/orbital.v10i1.1007